Stakeholder perceptions about the drivers, impacts and barriers of certification in the Ghanaian cocoa and oil palm sectors - Dompreh, E.B.; Asare, R.; Gasparatos, A. (Springer, 2021)
This perception mapping exercise elicits and synthesizes the perceptions of the main relevant stakeholder about the drivers, impacts, and challenges of cocoa and oil palm certification in Ghana. Through an institutional analysis, we identify the main stakeholders and elicit their perceptions through 36 expert interviews. Perceptions are rather diverse, reflecting stakeholder position in (and knowledge of) the certification processes for the two commodity crops. Most stakeholders perceive that market-related factors drive standard adoption, and financing-related constraints challenge their wide adoption. There are major trade-offs and power asymmetries in certification processes, manifesting differently, due to variations in the implementation approaches and overall regulations of the two value chains.